1985
DOI: 10.1111/j.1600-0447.1985.tb05047.x
|View full text |Cite
|
Sign up to set email alerts
|

Normal ventricles in chronic schizophrenics

Abstract: The computed tomography (CT) scans of 46 chronic schizophrenic patients and 46 controls were studied using ventricular-brain ratio. Ewans' index, and cella media index. None of the indices used revealed significant differences between the patient and the control groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1987
1987
1991
1991

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…A failure to reject the nu1 hypothesis of no difference between groups is never proof that no difference exists. The mean VBR in our control groups was much greater than those in other studies; only Shima et al (17) reported quite similar VBR size. This discrepancy might have derived from measurement, but in this case both patients and controls were examined in a uniform manner.…”
Section: Discussioncontrasting
confidence: 69%
“…A failure to reject the nu1 hypothesis of no difference between groups is never proof that no difference exists. The mean VBR in our control groups was much greater than those in other studies; only Shima et al (17) reported quite similar VBR size. This discrepancy might have derived from measurement, but in this case both patients and controls were examined in a uniform manner.…”
Section: Discussioncontrasting
confidence: 69%
“…An approach to this study would be to apply metaanalysis techniques to the result of 17 studies which used planimetric methods (1, 9, 15-17, 19, 22, 34-38, 43-46, and ours). The studies that used the density method were excluded (20, [47][48][49]. We also left out Johnstone's study (2) because of its unusually high VBR, and Rieder's study (50) because he did not use controls.…”
Section: Discussionmentioning
confidence: 99%
“…These have generally been unsuccessful in treating schizophrenia or have exacerbated symptoms. Interventions designed to decrease serotonergic activity, e.g., inhibition of 5HT synthesis with p-chlorophenylalanine (DeLisi et al 1982a) or fenfluramine, a 5HT releaser (Shore et al 1985), have also generally been ineffective.…”
Section: Serotonin and Schizophreniamentioning
confidence: 99%
“…This research has been reviewed in depth elsewhere (Shelton and Weinberger 1986). Although at least five studies have not found enlarged ventricles in schizophrenics (Trimble and Kingsley 1978; Glück et al 1980; Benes et al 1982; Jernigan et al 1982; Shima et al 1985), consideration of all available evidence suggests that there is an excess proportion of schizophrenics with ventricular size outside normal limits (Shelton and Weinberger 1986). Variability of results may be due to measurement differences or differences in clinical populations and control groups.…”
Section: Structural Abnormalities: Neuropathology and Ct Scansmentioning
confidence: 99%